(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the theoretical and methodological foundations of the development of pilgrimage tourism, which promotes the concept of cluster policy and integrated marketing in the development of the industry. One of the important factors in the development of tourism in our country is peace, stability, mutual understanding and solidarity.